Academic Procrastination of Chemistry Education Students Based on Gender Perspective - Nada, Ella Izzatin; Sari, Wiwik Kartika (Jurnal Pendidikan dan Pembelajaran Kimia, 2023)
After the pandemic, learning was again carried out offline, making students feel anxious and worried about the assignments given by the lecturers. Students' ability to manage time-related to self-discipline is needed during the transition from online to offline learning. This study aims to measure the level of post-pandemic student academic procrastination or delay based on a gender perspective. Gender analysis is crucial because men have synonymously carried out academic delays, so this research needs to be done. This study used a quantitative approach through a cross-sectional exploratory study involving comparative and correlation analysis. ‎ The population of this study was students of chemistry education at UIN Walisongo Semarang: semester 1, semester 3, and semester 5. The results showed no significant difference in academic Procrastination between male and female students (p > 0.05). The absence of this difference can be due to factors that influence individual development, such as physical, psychological development and social roles, so Procrastination is not determined by gender. DOI: 10.23960/jppk.v12.3.2023.07